Dengue Incidence and the Prevention and Control Program in Malaysia - Mudin, Rose Nani (IIUM Medical Journal Malaysia, 2015)
The trend of dengue incidence in the regions and many countries has shown an increasing trend for the past few decades. The World Health Organization (WHO) reported that the incidence increased dramatically over the last 50 years and that dengue virus infections expanded to new countries, and from urban to rural settings. Malaysia is one of the countries that experience similar situation. The trend of dengue incidence in Malaysia has continued to increase since 2001 until 2014. In 2001, the dengue incidence rate (IR) was 72 cases in 100,000 population and progressively increased to 361 cases in 100,000 populations in 2014. There were temporary decrease of the incidence rate in 2011 and 2012 to 69.9 and 76 cases per 100,000 populations. Despite the close monitoring and continuous efforts from the Ministry of Health and Municipals to conduct the prevention and control activities, the number of dengue cases continues to increase due to multiple uncontrolled factors. There are at least five major factors that influence the transmission of dengue disease which include the dengue virus, the human as the host, the environmental condition such as cleanliness, the vectors and its behavior and the climate change. Due to these multiple factors that influence the disease pathophysiology and transmission of dengue virus, the control of mosquito-borne viral infection is very challenging and different from managing other infectious diseases. In addition, the rapid urbanization, population growth and human behavior together with international travel, making the control of dengue transmission even more difficult. Based on the circumstances, Ministry of Health Malaysia has implemented the intergrated strategy for dengue prevention and control program in the National Dengue Strategic Plan (NDSP) since 2011. There are seven strategies included in the NDSP which is strengthening of the dengue surveillance, practicing intergrated vector management, emphasizing on the dengue case management, social and community mobilization towards the prevention activity, ensuring rapid response in managing the dengue outbreak and developing new innovative method through dengue research. Most of the factors that contribute to the occurrence of dengue cases are difficult to be controlled and these leave with only manipulation and intervention with the environment, vector control and changing the human behavior for the prevention and control of dengue.